2007
DOI: 10.1210/me.2006-0452
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/Enhancer Binding Protein β Abrogates Retinoic Acid-Induced Osteoblast Differentiation via Repression of Runx2 Transcription

Abstract: Runx2/CBFA1/AML3 is a master regulator of the osteoblast lineage and has been shown to directly control the transcription of numerous osteoblast-specific genes including alkaline phosphatase, osteopontin, and type I collagen. In its absence, ossification does not occur during development resulting in animals with cartilaginous skeletons and no osteoblasts. In humans, loss of one copy of Runx2 causes cleidocranial dysplasia characterized by malformations of the facial and cranial bones and the clavicle. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 45 publications
8
44
0
Order By: Relevance
“…Studies from the Wahli laboratory (59) have shown inhibition of peroxisome proliferator-activated receptor ␤expression by C/EBP␤ and its association with histone deacetylase in the control of differentiation and proliferation of keratinocytes. It can also bind directly to the C/EBP element on the osteoblast-specific Runx2 promoter independent of deacetylase activity to repress gene expression, resulting in an inhibition of retinoic acid-induced osteoblast differentiation (60). In our studies, C/EBP␤ at low concentrations enhances calcitonin-induced 1␣(OH)ase transcription, but at high concentrations repression of 1␣(OH)ase transcription was observed.…”
Section: Discussionmentioning
confidence: 45%
“…Studies from the Wahli laboratory (59) have shown inhibition of peroxisome proliferator-activated receptor ␤expression by C/EBP␤ and its association with histone deacetylase in the control of differentiation and proliferation of keratinocytes. It can also bind directly to the C/EBP element on the osteoblast-specific Runx2 promoter independent of deacetylase activity to repress gene expression, resulting in an inhibition of retinoic acid-induced osteoblast differentiation (60). In our studies, C/EBP␤ at low concentrations enhances calcitonin-induced 1␣(OH)ase transcription, but at high concentrations repression of 1␣(OH)ase transcription was observed.…”
Section: Discussionmentioning
confidence: 45%
“…The role of RA in osteoblastogenesis has been studied extensively in vitro and it has been shown to both promote and inhibit differentiation, as well as to drive bone matrix synthesis (Ahmed et al, 2000;Benayahu et al, 1994;Choong et al, 1993;Manji et al, 1998;Ohishi et al, 1995;Song et al, 2005;Wiper-Bergeron et al, 2007). Although variation between cell lines, the markers tested and experimental regimes might offer an explanation for these differing results, a clear consensus as to the role of RA has not emerged.…”
Section: Ra Signalling Is Required For Adipocyte Differentiation In Vivomentioning
confidence: 99%
“…Initially discovered as a regulator of IL-6 expression, C/EBP␤ has been implicated in numerous differentiation processes including adipogenesis, osteoblastogenesis, mammary gland development, and female fertility (7)(8)(9)(10)(11). Cebpb is an intronless gene that produces a single mRNA from a single promoter (12).…”
mentioning
confidence: 99%